Bloody Ridge and beyond : a World War II marine's memoir of Edson's Raiders in the Pacific - Groft, Marlin (Berkley Caliber, 2014)
"By a veteran of Lt. Col. Merritt A. Edson's battalion, and the author of the Dick Winters biography Biggest Brother and coauthor of A Higher Call. On the killing ground that was the island of Guadalcanal, a 2,000-yard-long ridge rose from the jungle canopy. Behind it lay the all-important air base of Henderson Field. And if Henderson Field fell, it would mean the almost certain death or capture of all 12,500 marines on the island. But the marines positioned on the ridge were no normal fighters. They were tough, hard-fighting men of the Edson's Raiders, an elite fighting unit within an already elite U.S. Marine Corps. Handpicked for their toughness, and submitted to a rigorous training program to weed out those less fit, they were the Marine Corps's best of the best. For two hellish nights in September 1942, about 840 United States Marines--commanded by Lieutenant Colonel Merritt Austin 'Red Mike' Edson--fought one of the most pivotal battles of World War II in the Pacific, clinging desperately to their position on what would soon be known as Bloody Ridge. Wave after wave of attacking Japanese soldiers were repelled by the Raiders, who knew that defeat and retreat were simply not possible options. But in the end, the defenders had prevailed against the odds. Bloody Ridge and Beyond is the story of the 1st Marine Raider Battalion, which showed courage and valor in the face of overwhelming numbers, as told by Marlin Groft, a man who was a member of this incredible fighting force"--